2005
DOI: 10.1093/rheumatology/keh679
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal physician adherence to quality indicators for the management of gout and asymptomatic hyperuricaemia: results from the UK General Practice Research Database (GPRD)

Abstract: One-quarter to one-half of all patients eligible for at least one of the validated quality of care indicators were subject to possible allopurinol prescribing error, suggesting that inappropriate prescribing practices are widespread with this agent. Future interventions aimed at reducing inappropriate allopurinol use are needed and should be targeted towards high-risk groups, including older men and those receiving multiple concomitant medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 26 publications
4
94
2
Order By: Relevance
“…The overall rate of 22% physician adherence to all 3 QIs is similar to results from the UKGPRD study that also examined 3 QIs. The QIs in the UK study included allopurinol use in patients with asymptomatic hyperuricemia, allopurinol dosing in renal failure, and concomitant allopurinol use in patients receiving azathioprine or 6-mercaptopurine (16). Our finding that 22% of patients with renal insufficiency received higher-thanrecommended allopurinol doses confirms the analogous rate of 25% in the UK study.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The overall rate of 22% physician adherence to all 3 QIs is similar to results from the UKGPRD study that also examined 3 QIs. The QIs in the UK study included allopurinol use in patients with asymptomatic hyperuricemia, allopurinol dosing in renal failure, and concomitant allopurinol use in patients receiving azathioprine or 6-mercaptopurine (16). Our finding that 22% of patients with renal insufficiency received higher-thanrecommended allopurinol doses confirms the analogous rate of 25% in the UK study.…”
Section: Discussionsupporting
confidence: 77%
“…It is of concern that 22% of our patients with renal insufficiency received higher-than-recommended allopurinol doses, similar to the 25% noncompliance rate found in an earlier study (16). Two previous studies reported inappropriately high allopurinol doses in patients with renal insufficiency, 47% in elderly adults (10) and 39% in adults (11).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although substantial attention in gout has been given to suboptimal adherence to quality-of-care indicators among providers (12)(13)(14) and low SU goal attainment among patients (15,16), to what extent patients understand gout and their treatment is largely unknown. Patients report that they are concerned, but uninformed, about whether or not ULT triggers gout attacks (17).…”
Section: Introductionmentioning
confidence: 99%